PTU-054 Outcomes following Investigation and Elective Withdrawal of Anti-TNF Therapy in Crohn'S Disease: a UK Multicentre Study. (4th June 2013) - Brooks, A J; Sebastian, S; Robinson, K; Warren, L; Wright, A; Marsh, A M; Tsai, H; Majeed, F; McAlindon, M E; Hamlin, P J; Lobo, A J
Abstract : Introduction: The impact of stopping anti-TNF for patients in clinical and/or endoscopic remission in routine clinical practise setting is uncertain. We aimed to evaluate clinical outcomes in patients who discontinued anti-TNF electively across 3 units in the Yorkshire & Humber IBD Network, UK. Methods: Crohn's disease (CD) patients in whom anti-TNF (62 infliximab (IFX), 9 adalimumab (ADA)) was stopped electively following a planned assessment were included. All had been treated for ≥ 12 months and followed-up for ≥ 3 months following cessation of anti-TNF. Investigations at assessment prior to cessation included ≥ 1 of; colonoscopy, colon capsule (CC), small bowel capsule (SBC), magnetic resonance enterography (MRE), barium study (BS), CRP and clinical assessment (CA). Results: Seventy-one patients (44 female; median age at diagnosis 24 years) were included with a median duration of IBD prior to anti-TNF of 24 (0–264) months. Indications were severe active luminal (50/71), fistulating perianal (18/71) and other fistulating disease (3/71). The median treatment duration was 18 months (range 12–78) with 62 (87%) on immunomodulators post anti-TNF withdrawal. Relapse rates within 90, 180 and 365 days were 3/71(4.2%), 14/67(21%) and 27/57(47%) respectively. In perianal disease alone, the relapse rate was 6/18 (33%) at 1 year. 25 of those who relapsed were retreated with anti-TNF, with an overall recapture rate of 84%. In those retreated with the same agent as previously withdrawn the response rate was 80%. A further 5 were successfully retreated with ADA when IFX had been withdrawn. Those (6) who had a dose escalation in 6 months prior to withdrawal all relapsed. Assessment practise changed following NICE guidance in 2010. Prior to this 5/15(33%) stopping anti-TNF had a CA alone. Following NICE guidance 2/56 (3.6%) were assessed only by CA. Investigations to complement routine CA by Harvey Bradshaw Index (HBI), included ≥ 1 of colonoscopy (52), CC (4), MRE (19), SBC (5), BS (2) and CRP (66). HBI ≥ 4 and a CRP of ≥ 5 in the 6 months prior to formal assessment was observed in 26 patients. 14/26 (54%) relapsed following cessation of anti-TNF (positive predictive value of 61%). Further invasive investigations in this group were abnormal in 2 patients. Conclusion: In this UK cohort, elective withdrawal of anti-TNF was associated with a relapse rate of 48% after 12 months, with a high retreatment response rate. Due to NICE guidance, increased invasive assessment occurred, but the role of endoscopy and imaging to evaluate remission prior to withdrawal of anti-TNF needs further evaluation. Disclosure of Interest: A. Brooks: None Declared, S. Sebastian Conflict with: Dr Sebastian has participated in advisory boards and received speakers honoraria, educational and research grants from Abbott and MSD, K. Robinson: None Declared, L. Warren: None Declared, A. Wright: None Declared, A. Marsh: None Declared, H. Tsai Conflict with: Dr Tsai has participated in advisory boards and received speakers honoraria, educational and research grants from Abbott and MSD, F. Majeed: None Declared, M. McAlindon: None Declared, P. Hamlin Conflict with: Dr Hamlin has participated in advisory boards and received support for specialist nurses from Abbott and MSD, A. Lobo:None Declared